The Noise Performance of a Multiple-Input-Port and Multiple-Output-Port Low-Noise Amplifier Connected to an Array of Coupled Antennas - Frédéric Broydé; Evelyne Clavelier (International Journal of Antennas and Propagation)
We address the noise characterization of a multiple-input-port and multiple-output-port (MIPMOP) device receiving signals from an array of antennas. A definition of the noise figures and natural noise figures of a MIPMOP device is provided, and the resulting properties are detailed in the impedance and admittance representations. We compute the natural noise figures of a low-noise MIPMOP amplifier comprising a MIMO series-series feedback amplifier (MIMO-SSFA), designed for a wireless receiver front-end.